Characterization and Identification of Allergen Protein in Shrimp Before and After Heated with SDS-PAGE Method - Emma Emawati; Idar Idar; Resta Ramadiyanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Food allergies are one of the most common allergies in Indonesian society. Generally, when children aged 5-6 years food allergies will disappear, except peanut allergies and allergies to seafood, such as fish, shellfish and crustaceans. This study aims to determine the pattern of separation of allergen proteins in shrimp using anion exchange column chromatography method and identify allergen proteins in shrimp using the sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) method. Protein extraction from shrimp using Phosphate buffer saline (PBS) pH 7.2 and centrifuged at 10,000 rpm for 10 min at 4°C. Protein separation was carried out by anion-exchange column chromatography method, and the fraction obtained was measured at 280nm wavelength. The highest yield at absorbance was identified by using SDS-PAGE. Polyacrylamide gel electrophoresis was used to determine the protein profile and molecular weight of shrimp extract. Coloring of protein bands using silver staining. Data were analyzed descriptively based on the migration value of the sample protein bands compared to the marker protein band (Rf). The results of protein allergen profile analysis on shrimp using SDS-PAGE showed that the shrimp contained a protein band with a molecular weight of 37.77 kDa for cooked shrimp and 37.03 kDa for fresh shrimp.